Comparison of sensory attributes and chemical markers of the infrared spectrum between defective and non-defective Colombian coffee samples - Barrios Rodriguez, Yeison Fernando; Salas Calderon, Karen Tatiana; Giron Hernandez, Joel (Coffee Science - ISSN 1984-3909, 2020)
Defects in coffee affect the sensory quality of finished drink. To avoid this, defective beans are usually removed after threshing, as, once the green beans have been roasted, it becomes difficult to identify the defects. Procedures have been developed to evaluate coffee samples using infrared spectroscopy to detect such defects. As such, this study evaluated infrared spectra and sensory attributes of 39 coffee samples in: commercial ground and instant coffees, medium and high roast quality coffees, and defects present in the coffee. The sensory analysis was performed by 10 judges, semi-trained by a Q-grader, and eleven attributes were assessed using a semi-structured hedonic scale. The spectra obtained from the coffee samples were processed by area normalization, first derivative, and second derivative, later followed by principle component analyses. The sensory results showed differences in the evaluated attributes, differentiating between the samples of high quality medium roast coffee from the other samples. Principal component analysis applied to IR spectra showed that when normalizing the data by area, the samples were discriminated, which explained 84% of variance; coffee defects in the samples of ground commercial coffee were separated from high quality coffee and instant coffee. Using the chemical descriptors obtained from the infrared spectra, it was possible to differentiate between high quality, commercial and instant coffee. Key words: Coffee bean defects; FTIR-ATR; principal component analysis; quality coffee.